Causes of Aviation Accidents and Incidents Especially with Engine Failure - Krejsa, Tomáš; Němec, Vladimír; Hrdinová, Lenka (Kaunas University of Technology, 2018)
Air transport is the safest and the most dynamic mode of transport but there are errors that can lead to aviation accidents or incidents. This paper deals with explanations of basic concepts in the field of aviation safety, states organizations that are involved in ensuring the safety of the aviation industry, including Safety management system. The main idea of this article is to analyze the causes of air accidents and incidents during the ten-year period, especially focusing on the causes of aircraft engine failure. Based on the identified primary causes of aircraft engine failure, authors propose measures that ultimately lead to increased safety in aviation.
Příčiny leteckých nehod a incidentů zejména při selhání motoru
Keywords: Air transport; safety; aviation accidents; aviation incidents; engine failure; Letecká doprava; bezpečnost; letecké nehody; letecké incidenty; selhání motoru